Mapping the Trap‐State Landscape in 2D Metal‐Halide Perovskites Using Transient Photoluminescence Microscopy. Issue 18 (4th February 2021) - Seitz, Michael; Meléndez, Marc; Alcázar‐Cano, Nerea; Congreve, Daniel N.; Delgado‐Buscalioni, Rafael; Prins, Ferry
Abstract: Transient microscopy is of vital importance in understanding the dynamics of optical excited states in optoelectronic materials, as it allows for a direct visualization of the movement of energy carriers in space and time. Important information on trap‐state dynamics can be obtained using this technique, typically observed as a slow‐down of energy transport as carriers are trapped at defect sites. To date, however, studies of the trap‐state dynamics have been mostly limited to phenomenological descriptions of the early time‐dynamics. Here, it is shown how long‐acquisitiontime transient photoluminescence microscopy can be used to provide a detailed map of the trapstate landscape in 2D perovskites, in particular when used in combination with transient spectroscopy. An anomalous evolution of the studied exciton distribution is observed, which cannot be explained with existing models for trap limited exciton transport that only account for a single trap type. Instead, using a continuous diffusion model and performing Brownian dynamics simulations, it is shown that this behavior can be explained by accounting for a distinct distribution of traps in this material. These results highlight the value of transient microscopy as a complementary tool to more common transient spectroscopy techniques in the characterization of excited state dynamics in semiconductors. Abstract : Transient photoluminescence microscopy (TPLM) is presented as a complementary characterization method for the trap‐state landscape in 2D perovskites. By resolving the dynamics in space and time, anomalous diffusion is revealed that cannot be explained using existing models. Here, it is shown that the behavior originates from a distinct trap‐state distribution, emphasizing the value of TPLM as a characterization tool.